Diseño e Implementación de un contador de vehículos para la gestión de estacionamientos en la ciudad de Loja - Loja Reyes, Santiago José (2023)
This project focuses on a vehicles counter for a parking lot management in the city of Loja. We designed a prototype with the purpose to count vehicles that enter inside a parking lot which uses Arduino a system that has the function of detecting the vehicles, and NodeMCU ESP8266 as communication system for sending data, and the implementation of a mobile application compatible with Android devices. The research work has three phases. The first phase consists of the design for the connection and programming of the prototype with the development boards and the proximity sensors used. The second phase consists of the implementation of a mobile application, which coordinates the communication of the prototype with a web server that allows sending the data by means of an ID as an identifier to be able to visualize the information of the parking lot where the prototype is located. The third phase is analyzed by means of a vehicular flow analysis; data was obtained on the number of vehicles passing through an intersection to determine the number of vehicles circulating on city streets at peak hours. In this way, it has been possible to develop a prototype that integrates sensors, programming, wireless communications, web applications and statistical analysis to demonstrate how the implementation of new technologies is the solution to traffic and mobility problems in cities. Keywords: Parking lots, Vehicular flow, vehicle detection, Traffic, Mobility.